Genetic Diversity Between Exotic And Nigerian Indigenous Turkey At Different Structural Loci (2018)
Poultry genetic resources in general are considered to be the most endangered and under-conserved, detailed attention is therefore needed on the existing genetic resources to reduce or prevent the increasing genetic erosion of local livestock. This study was conducted to characterize and estimate genetic diversity in Nigerian indigenous turkey and exotic turkey using blood proteins (Haemoglobin, Transferrin and Albumin) and enzyme (Carbonic Anhydrase and Esterase 1) markers. A total of 110 turkeys comprising 50 Nigerian indigenous turkeys and 60 exotic turkeys were used for the analysis. Separation of blood protein genotypes was achieved using cellulose acetate electrophoresis. The populations were characterized for their genetic variability using allele frequencies, observed heterozygosity, F-statistics (FIT, FIS, FST), test for Hardy-Weinberg and Genetic distance. Eleven variants were found at the five loci studied, two co-dominant allele A and B controlling three genotypes AA, AB, and BB were observed at Haemoglobin, Carbonic Anhydrase, Albumin and Esterase1 loci for both indigenous and exotic turkey breeds, a third allele C was observed in Transferrin locus. Allele A was the most frequency at the Hb, CA, Alb and Es1 locus in Nigerian indigenous turkey with frequencies 0.541, 0.541, 0.520, and 0.520 respectively and exotic turkey at Hb, Alb, and Es1 with frequencies 0.508, 0.617, and 0.508 respectively. Chi Square result indicated deviations from Hardy Weinberg equilibrium in the two populations. The average heterozygosity values were 0.56 and 0.477 indicating high genetic variability, heterozygote excess FIT was estimated at -0.050 while within breed excess as evaluated by FIS ranged from 0.370 to -0.336. The fixation index FST revealed that genetic diversity within the studied population was slightly differentiated. Genetic distance among the populations quantified through calculation of Nei’s Genetic distance was 0.008 while the identity was 0.992. Similarity in the estimated genetic variability parameters between the breeds indicates that the populations are closely related and there were no appreciable differences among them. This result obtained may be used as an initial guide in defining objectives for further investigations of genetic diversity and developing conservation strategies.